The effect of speed training on sprint and agility performance in female youth soccer players - Mathisen, G.; Pettersen, S. A. (Journal of Physical Education and Sport, 2015)
The main aim of this study was to investigate the effects of short burst speed and change-of -direction exercises on sprint and agility performance in youth female soccer players 15.5 (± 0.7) years. One training group (n=10) followed an eight-week, once per week training program consisting of short-burst sprinting exercises in addition to two normal soccer training, while a control group (n=9) followed three traditional soccer training session. Preand post-tests assessed significant improvement in 10 m sprint, pre 1.99 s (± 0.08), post 1.91 s (± 0.09), 20 m sprint pre 3.53 s (± 0.15), post 3.42 s (± 0.15), and agility performance, pre 8.23 s (± 0.31), post 7.80 s (± 0.33). Control group (15.1 years (± 0.7) did not demonstrate significant change in performance during the intervention period. The results demonstrate that a training program of short burst high speed exercises improve linear sprint and agility performance in youth female soccer players, beyond the gain of traditional soccer training consisting of small-sided games.